2021
DOI: 10.1590/0037-8682-0610-2020
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and spatial study of visceral leishmaniasis in the state of Alagoas, Brazil, during 2007-2018

Abstract: Introduction: Visceral leishmaniasis has a broad worldwide distribution and constitutes a public health problem in the Northeast of Brazil. Located in this region is the state of Alagoas, where the disease is endemic in humans and where there has been a significant increase in the number of positive dogs. The objective of this study was to describe the temporal and spatial distribution of the cases of human VL in the state of Alagoas with the aim of identifying transmission risk areas in the period from 2007 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Another study, which had the state of Alagoas as its analysis space, confirms a progressive evolution of VL incidence rates in the Federation Unit, showing geographic expansion, a trend of zoonosis persistence in areas that already had reported cases, and overall strengthening of the endemic status of the disease in that territory between 2007 and 2018 20 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another study, which had the state of Alagoas as its analysis space, confirms a progressive evolution of VL incidence rates in the Federation Unit, showing geographic expansion, a trend of zoonosis persistence in areas that already had reported cases, and overall strengthening of the endemic status of the disease in that territory between 2007 and 2018 20 .…”
Section: Discussionmentioning
confidence: 79%
“…The differences between the behavior of national and federation units' incidence rates suggest that different factors can influence the risk of VL among states and regions of the country. Rocha et al 29 , Braz et al 20, and Ribeiro et al 30 agree that the behavior of this zoonosis in the regions of the country is directly associated with the environmental and geographic conditions of the territory, where situations of high temperature and humidity predominate, which enable a good adaption and reproduction of the vector; and precarious socio-environmental issues such as lack of basic sanitation and water supply, poor housing conditions, accumulation of waste from the peridomicile both in an urban and rural area, the intense population of vectors and canine cases of the disease, presence of livestock close to residences and proximity of households to green areas, factors that directly interfere in the adaptation and reproduction of L. longipalpis.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission cycle that used to take place in a wild and rural environment, today intensifies in urban centers. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Human visceral leishmaniasis (VL) is endemic in Brazil [1][2][3][4][5][6][7][8][9][10][11][12] and is recognized as a neglected tropical disease by the World Health Organization [13]. In Brazil, VL etiology stems from the protozoan Leishmania infantum, where the domestic dog serves as a sentinel host with the phlebotomine sand fly as the typical vector [14].…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al [ 6 ] reported increasing VL cases from 2012 to 2017 in major cities of the Paraíba state in Brazil, Almeida et al [ 19 ] observed spatial expansion of VL from 2007 to 2017 in Fortaleza, a coastal city within the Ceará state in Brazil, and da Silva Lima et al [ 20 ] noted increasing VL fatality in the last decade in Piauí, Brazil. The state of Alagoas, Brazil also experienced geographic spread of VL from 2007 to 2018, primarily in rural areas [ 7 ]. Such trends warrant government awareness and require results from improved statistical modeling to better understand, and inform, the dynamics of VL transmission patterns to guide public health policy.…”
Section: Introductionmentioning
confidence: 99%